INTERACTIVE METHODS OF TEACHING ENGLISH IN A SUMMER CAMP - Shevchenko, Svitlana (Mountain School of Ukrainian Carpaty, 2020)
The article deals with the problem of interactive methods introduction in the process of teaching English in summer camps with the programs of realization the tasks of recreation, recovery and learning English. The author gives an outline of the main tasks and types of interactive activities which are popular in a summer camp to reinforce autonomy and motivation of children. All the examples given in the article were introduced in the summer camp “Forest song”, Yakymivka district Zaporizhzhia region by the members of international organization AISEC. Brainstorming technique, pair work, role play, quests, mingle tasks, project work, outdoor games are the most popular interactive tasks and activities in a summer camp. Interactive tasks and activities are considered as effective methods to improve the quality of foreign language teaching and learning. Besides, the role of the interactive methods of teaching is stressed as to their positive effect not only at language competence but some personal characteristics and interrelations within a group of children as well. Interactive methods enable not to forget that every learner is unique and brings to the process of education his/her personal opinion, point of view and attitude. Interactive classes have atmosphere of educational interaction between a learner and an educator that, in its turn; effects positively at the quality of learning English language. Interactive methods of teaching English in a summer camp with foreign volunteers, capable to remove communication barriers, help to overcome psychological discomfort, raise self-assessment, improve memory and creative way of thinking, develop respect for the representatives of different cultures, tolerance, and ethical behavior.